Separation of Regional and Residual Anomalies Using GGMPlus Gravity Data in Panti Sub-District, West Sumatra - Putri Yasmin; Pakhrur Razi; Yuta Izumi (MASALIQ, 2025)
This study addresses the limited application of GGMPlus satellite gravity data for regional and residual anomaly separation in geothermal exploration within Indonesia. The research aims to separate and analyze gravity anomalies to elucidate subsurface geological structures in Panti District, Pasaman Regency, West Sumatra. A quantitative-descriptive approach with an exploratory design was employed, utilizing secondary gravity data from the GGMPlus model comprising 4,537 measurement points at 200-meter intervals. Data processing involved Bouguer correction, Fourier transformation, and the application of a bandpass filter using Oasis Montaj software. The complete Bouguer anomaly in the study area ranges from –37.5 to –25.6 mGal. Frequency-based separation yielded regional anomalies ranging from –37.3 to –25.8 mGal, while residual anomalies varied between –0.77 and 0.72 mGal. The residual anomalies are interpreted as responses from shallow subsurface features, including sedimentary rocks and potential geothermal reservoirs. In contrast, the regional anomalies are associated with deeper geological structures, such as faults and intrusive bodies. These findings demonstrate that frequency-domain filtering provides an effective means of enhancing the interpretability of satellite-derived gravity data in geothermal investigations. The study confirms the utility of GGMPlus data and spectral filtering techniques in delineating subsurface targets and improving geophysical assessments for geothermal resource exploration.